STIMULASI PERKEMBANGAN ANAK MELALUI PERMAINAN TRADISIONAL SUKU BATAK TOBA - Ivo Yani (JIV-Jurnal Ilmiah Visi, 2017)
Traditional games are ancestral estates that need to be maintained and preserved. Rarely are they played in PAUD due to the fact that they have been replaced by modern games, whereas there are a lot of traditional games in every region. The Batak Toba traditional games can stimulate both motor skills and social-emotional development in early childhood. Types of games researched are Marsibahe, Marsitekka, and Marampera. This research aims to find out results on motor skills and social-emotional stimulation in early childhood through Batak Toba traditional games. The research was conducted to 18 children in a range of 5-6 years old in PAUD Anugerah in Tomok Village, Simanindo District, Samosir District in July-October 2015. The data collection instrument is arranged based on their achievement levels of motor skills and social-emotional development referring to Permendikbud No. 137 in 2014 as many as 16 points of observation. A quasi-experiment design method with pretest and posttest is used to recognize field validation, meanwhile the significant of the program is examined by using a correlated t-test. The results show t > t (10.34 > 2.11) so that it can be inferred that there are significant changes on score acquired by the learners before and after playing Batak Toba traditional games at 5% significant level.